Are eye‐care practitioners fitting scleral contact lenses?. (9th June 2020) - Woods, Craig A; Efron, Nathan; Morgan, Philip; ,
Abstract : Background: To determine the extent of scleral lens fitting worldwide and to characterise the associated patient demographics. Methods: Survey forms were sent to contact lens fitters around the world, every year for 20 consecutive years (2000 to 2019). Practitioners were asked to record data relating to the first 10 contact lens fits or refits performed after receiving the survey. Data were analysed for those countries reporting ≥ 1, 000 contact lens fits during this period. Results: A total of 369, 209 contact lens fits were recorded from 40 eligible countries, comprising 2, 309 scleral lens fits and 366, 900 other (non‐scleral) lens fits. Overall scleral lenses represented 0.76 per cent of all contact lens fits with significant differences between countries (p < 0.0001), ranging from no fits in six countries: Hungary, Indonesia, Iran, Korea, Malaysia and Singapore, to 5.9 per cent in Switzerland. There has been an increase in scleral lens fitting over the survey period (p < 0.0001), with the rate of fits increasing from negligible (< 0.50 per cent) before 2006 and then increasing from 2011 onward (p < 0.0001). Scleral lenses were fit to older patients (38.5 ± 15.0 years) compared to other lenses (31.4 ± 13.7 years) (p < 0.0001), this age disparity increasing over the survey period (p < 0.0001) and were more likely to be males (scleral lens fits 53 per cent, non‐scleral lenses 33 per cent, p < 0.0001). The increase in scleral lens fits is commensurate with the increase in related publications in the peer‐reviewed literature over the same period (p < 0.05, r 2 = 0.82). Conclusion: Scleral lens use has increased since 2011 with these specialised lenses more likely to be fitted to males and older patients than non‐scleral lenses.